2018
DOI: 10.3389/fimmu.2018.01585
|View full text |Cite
|
Sign up to set email alerts
|

Antigen-Specific CD4+CD8+ Double-Positive T Cells Are Increased in the Blood and Spleen During Ehrlichia chaffeensis Infection in the Canine Host

Abstract: Ehrlichia chaffeensis is an obligate intracellular bacterium belonging to the order, Rickettsiales and is a frequent cause of severe and fatal tick-borne infection in people in North America. The reservoir host for E. chaffeensis is the white-tailed deer, while humans and dogs are regarded as common incidental hosts. In dogs, we and others have shown that E. chaffeensis establishes a chronic infection that persists for several weeks to months, while promoting the development of Th1 and Th17 cellular responses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 58 publications
0
12
0
Order By: Relevance
“…These studies aided in the identification of one mutation in ECH_0660 gene causing the rapid clearance of the pathogen and inducing a sufficient host immune response to serve as a live attenuated vaccine to protect against wild type infection challenge by intravenous (IV) infection, as well as by tick transmission (16,17). Mutagenized E. chaffeensis organisms are also valuable in studies focused on understanding the host response against the pathogen (17,18).…”
Section: Impact Of Mutations On the Rna Expression For Gene Disruptiomentioning
confidence: 99%
See 1 more Smart Citation
“…These studies aided in the identification of one mutation in ECH_0660 gene causing the rapid clearance of the pathogen and inducing a sufficient host immune response to serve as a live attenuated vaccine to protect against wild type infection challenge by intravenous (IV) infection, as well as by tick transmission (16,17). Mutagenized E. chaffeensis organisms are also valuable in studies focused on understanding the host response against the pathogen (17,18).…”
Section: Impact Of Mutations On the Rna Expression For Gene Disruptiomentioning
confidence: 99%
“…We further reported that Himar1 transposase-based random mutagenesis is efficient in creating mutations in both protein-coding and noncoding regions of the pathogen ( 14 ). We demonstrated that Himar1 mutagenesis is a valuable tool in elucidating host-pathogen interactions and in developing attenuated mutant vaccines ( 16 18 ). Similarly, random mutagenesis is described for other members of the alphaproteobacterial order Rickettsiales ( 19 24 ).…”
Section: Introductionmentioning
confidence: 99%
“…In swine, DP T cells are a multifunctional memory T cell subset involved in protection against viral infections (Gerner et al, 2015;Okutani et al, 2018), while in humans this T cell subset is associated with chronic diseases, including atopic dermatitis (Bang et al, 2001;Overgaard et al, 2015). Only a few reports describe these CD4+CD8+ DP T cells in dogs and they seem to have an activated phenotype (Bismarck et al, 2012(Bismarck et al, , 2014Hoshino et al, 2008;Kato et al, 2007;McGill et al, 2018), but their function remains largely unclear. Recently, canine CD4+CD8+ DP T cells were shown to expand upon infection with Ehrlichia chaffeensis, an obligate intracellular bacterium causing chronic infections in dogs (McGill et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Only a few reports describe these CD4+CD8+ DP T cells in dogs and they seem to have an activated phenotype (Bismarck et al, 2012(Bismarck et al, , 2014Hoshino et al, 2008;Kato et al, 2007;McGill et al, 2018), but their function remains largely unclear. Recently, canine CD4+CD8+ DP T cells were shown to expand upon infection with Ehrlichia chaffeensis, an obligate intracellular bacterium causing chronic infections in dogs (McGill et al, 2018). In our study, dogs with AFR had a higher baseline value of DP T cells than that reported in healthy dogs (25% vs 2.4%, resp.)…”
Section: Resultsmentioning
confidence: 99%
“…CD4 + CD8 + dp T cells have been identified in dogs with and without CanL ( 56 , 90 , 91 ). In the current study, the frequency of CD4 + CD8 + dp T cell subsets was revealed to be increased in peripheral blood, lymph node, and bone marrow of dogs with CanL.…”
Section: Discussionmentioning
confidence: 99%